2020
DOI: 10.3389/fphar.2020.01307
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Heparin in Patients With COVID-19: Beyond the Anticoagulant Effect. A Review

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is responsible of variable clinical manifestations, ranging from no symptoms to severe pneumonia with acute respiratory distress syndrome, septic shock, and multi-organ failure resulting in death. To date no specific antiviral drug have been approved for COVID-19, so the treatment of the disease is mainly focused on symptomatic treatment and supportive care. Moreover, there are no treatments of proven efficacy to reduce the progression of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 93 publications
(104 reference statements)
3
64
0
3
Order By: Relevance
“…Another remarkable candidate for the treatment of COVID-19 is LMWH, with the aim to improve the coagulation dysfunction of COVID-19 [ 63 , 64 ]. Really, during the course of SARS-CoV-2 infection, an increased incidence of acute pulmonary embolism episodes was detected.…”
Section: Discussionmentioning
confidence: 99%
“…Another remarkable candidate for the treatment of COVID-19 is LMWH, with the aim to improve the coagulation dysfunction of COVID-19 [ 63 , 64 ]. Really, during the course of SARS-CoV-2 infection, an increased incidence of acute pulmonary embolism episodes was detected.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies that propose heparin treatment for COVID-19 patients [ 44 , 45 ]. Recently, it has been suggested that heparin might have therapeutic potential against SARS-CoV-2 infection as a competitive inhibitor [ 45 , 46 , 47 , 48 ]. Our study supports the used of heparin as treatment of choice in COVID-19, especially in SCI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Heparin inhibits the activation of the fibrin stabilizing factor through a trombone, which prevents the fibrin clot formation. Anticoagulants, in particular heparin, are suggested for patients with severe COVID-19 ( Driggin et al, 2020 ; Gozzo et al, 2020 ). Since severe hypercoagulability occurs in these patients, early treatment with anticoagulation may decrease coagulopathy and reduce the risk of organ damages.…”
Section: Anticoagulantmentioning
confidence: 99%